The Effectiveness of the Level of Educational Knowledge Vulva Health Hygiene About Primary Prevention Cervical Cancer in Female Personnel at Indonesian Coast Guard, Jakarta - Indah Yuliani; Nurul Hidayah (Universitas Pahlawan Tuanku Tambusai, 2026)
Cervical cancer is still a major health problem in women, so primary prevention through increasing reproductive health knowledge, including vulvar hygiene, is very necessary. The results of observations in the female personnel of Bakamla RI showed that of the 81 participants who underwent Pap smears, 29 people (35.8%) experienced inflammation, which indicates a potential reproductive health problem. This condition shows that even though early detection has been carried out, the reproductive health knowledge of Bakamla RI female personnel still needs to be improved through health education as an effort to prevent cervical cancer. This study uses a quantitative method with Pretest-Posttest Design. The sample is 20 female personnel of Bakamla RI. The test used is the Wilcoxon Statistical Test. The results of the pre-test showed that the level of knowledge of the respondents still varied with an average score of 61.75, which reflects that the respondents' understanding of the Vulva Hygiene material was not optimal. After being given a health education intervention, the results of the post test showed a significant increase with the average score increasing to 97.25 and all respondents were in the category of good knowledge. Statistical analysis using the Wilcoxon Signed Rank Test test resulted in a value of p = 0.000 (< 0.05), which shows a significant difference between the level of knowledge before and after being given health education. Thus, health education on Vulva Hygiene delivered through leaflet and phantom media is an effective educational method as a primary prevention of cervical cancer in female personnel within the Maritime Security Agency of the Republic of Indonesia.This study shows that health education interventions can effectively increase knowledge about vulvar hygiene as a primary prevention strategy for cervical cancer among female personnel of Bakamla RI. Increased knowledge suggests that structured health education plays an important role in strengthening understanding of reproductive health and preventive behaviors. These findings support the integration of health education programs as a routine and strategic approach to improve cervical cancer prevention efforts among women in the workplace.